INTEGRASI KONSEP ALTRUISME DAN PENDIDIKAN ISLAM (Pendekatan Psikologi dalam Membangun Generasi Berkarakter) - Arifin, Faiz (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2024)
Altruism is the behavior of loving and treating others kindly without personal interest or expecting a reward. Altruistic attitudes involve behaviors such as sharing, helping, being kind, and collaborating. The implementation of altruism in Islamic religious education is crucial for creating a generation with noble character. This study is a library research aimed at understanding the implementation of altruism concepts in shaping the character of the younger generation, effective methods and strategies for teaching altruism to students, and the impact of implementing altruism on students' morals and character. The research results show that attitudes of care, empathy, and positive actions help students internalize humanitarian values. Through project-based learning methods, discussions, and social activities, students practice religious teachings in daily life, developing a character that is sensitive to the needs of others, as well as important social skills. The long-term impact is students' ability to face challenges with empathy and collaboration, as well as their readiness to become caring and responsible leaders.